Hsa_circRNA_100146 Promotes Prostate Cancer Progression by Upregulating TRIP13 via Sponging miR-615-5p - Zeng, Liang; Liu, Yi-min; Yang, Ning; Zhang, Tao; Xie, Huang (Frontiers in Molecular Biosciences, 2021)
Abstract. – OBJECTIVE: This study was conducted for investigating the functions of circular RNAs circRNA_100146 (circRNA_100146) in the development of prostate cancer (PCa) and identifying the underlying mechanisms of the circRNA_100146/miR-615-5p/TRIP13 axis. MATERIALS AND METHODS: Under the support of RT-PCR, the expression of circRNA_100146 in PCa cells was examined. Cell counting kit-8 (CCK-8) assays and clone formation assays were applied to the assessment of cell proliferation. We then determined cell invasion and migration through Transwell assays and Wound healing assays. RNA-pull down assays and Luciferase report assays were performed for the exploration of the regulatory effects of potential molecules on the expressions of the targeting genes. In addition, a nude mouse xenograft model was applied to demonstrate the oncogenic roles of circRNA_100146 in PCa. RESULTS: CircRNA_100146 expression was distinctly upregulated in PCa cells. Silencing of circRNA_100146 suppressed PCa cells’ invasion, migration and proliferation. CircRNA_100146 sponged miR-615-5p to suppress its expressions, while miR-615-5p targeted the 3’-UTR of TRIP13 to repress the expression of TRIP13. In addition, we observed that knockdown of miR-615-5p reversed the suppression of circRNA_100146 silence on the proliferation and invasion of PCa cells. In addition, the tumor growth was also suppressed by silencing circRNA_100146 in vivo. CONCLUSION: CircRNA_100146 is a tumor promotor in PCa, which promoted progression by mediating the miR-615-5p/TRIP13. CircRNA_100146 can be a potential candidate for targeted therapy of PCa.